O českém údělu - Jan Zouhar (Musicologica Brunensia, 2011)
A number of Czech intellectuals expressed their opinions on the meaning of Czech national existence in the late 1960s: Milan Kundera in his speech at the 4th congress of the Union of Czech Writers in June 1967, Karel Kosík in his essay Naše nynější krize (Our Current Crisis) in the spring of 1968, and a discussion opened between the Christmas of 1968 and the spring of 1969, after the invasion of Soviet army, in which Milan Kundera, Václav Havel, Karel Kosík, Jaroslav Střítecký and Lubomír Nový took part. The discussion was a reaction to the disappointment resulting from the suppression of the hopes of the Czechoslovakian spring of 1968 and critically reflected the situation in Czechoslovakian society.